2021
DOI: 10.1093/ofid/ofaa656
|View full text |Cite
|
Sign up to set email alerts
|

Candida Empyema Thoracis at Two Academic Medical Centers: New Insights Into Treatment and Outcomes

Abstract: Background Candida empyema thoracis (pleural empyema) is an uncommon manifestation of invasive candidiasis, for which optimal treatment is unknown. Methods This is a retrospective study of patients with Candida empyema at 2 academic medical centers from September 2006 through December 2015. Results We identified 81 patients with Candida empyema (median age, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…The identified risk factors for the development of Candida empyemas include elderly age, underlying comorbidities (such as diabetes mellitus, chronic kidney disease, cirrhosis, and malignancies), septic shock, receipt of steroids or chemotherapy, prolonged antibiotic use, ICU stay, and intra-abdominal diseases (such as esophageal rupture, complicated surgery, pancreatitis, etc.) [2,[7][8][9]. The distribution of Candida species in large case series describing the entity of fungal empyemas has shown that a majority are secondary to C. albicans, while NAC are less common [2,7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The identified risk factors for the development of Candida empyemas include elderly age, underlying comorbidities (such as diabetes mellitus, chronic kidney disease, cirrhosis, and malignancies), septic shock, receipt of steroids or chemotherapy, prolonged antibiotic use, ICU stay, and intra-abdominal diseases (such as esophageal rupture, complicated surgery, pancreatitis, etc.) [2,[7][8][9]. The distribution of Candida species in large case series describing the entity of fungal empyemas has shown that a majority are secondary to C. albicans, while NAC are less common [2,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…[2,[7][8][9]. The distribution of Candida species in large case series describing the entity of fungal empyemas has shown that a majority are secondary to C. albicans, while NAC are less common [2,7,8]. However, the ongoing shift in prevalence of NAC may alter the epidemiology of this condition in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between bacterial and viral superinfections and the development of CAPA in ICU COVID-19 patients has not been specifically investigated [ 19 , 26 , 34 ]. It is likely that the logistical difficulties associated with the pandemic spread have made the multi-resistant Gram-negative bacteria superinfections particularly frequent and severe [ 46 , 47 ]. To date, only one study [ 34 ] specifically addresses the issue of the possible correlation between previous broad-spectrum antibiotic therapy (notably carbapenems) and fungal superinfections.…”
Section: Discussionmentioning
confidence: 99%
“…Candida empyema was associated with prolonged mechanical ventilation and pulmonary thromboembolism. A recent review of Candida empyema thoracis attributed most cases to thoracic surgery, pleural instrumentation, and esophageal rupture [ 28 ], whereas this disease is rare in mechanically ventilated patients without prior pleural manipulation. Our findings suggest that thoracic Candida empyema could occur in critically ill COVID-19 patients due to prolonged mechanical ventilation, lung parenchymal necrosis, barotrauma, and overt or occult bronchopleural fistula formation [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%